ESTIMATION OF SECONDARY METABOLITES AND METHANE EMISSIONS IN SORGHUM SILAGE - Melchor Rosas-Davila; Ernesto Morales-Almaraz; Felipe Lopez-Gonzalez; Carlos Manuel Arriaga-Jordan (Tropical and Subtropical Agroecosystems)
Background. Feeding cattle in small-scale silage-based dairy production systems can improve their production efficiency while reducing greenhouse gas emissions. Objective. To determine the effect of partial replacement of corn silage with sorghum silage on the concentration of secondary metabolites in terms of Total Phenols (TP), Total Tannins (TT), and Condensed Tannins (CT), as well as to estimate methane (CH4) and carbon dioxide (CO2) emissions. Methodology. The treatments were analyzed with a split-plot experimental design where the treatments (main plot) were; T1 = 50% sorghum silage cv Top Green + 50% corn silage, T2 = 50% sorghum silage cv Caña Dulce + 50% corn silage, T3 = 100% corn silage cv Cenzontle (control), and the measurement periods were the minor plots. Results. Inclusion of sorghum silage decreased enteric methane and carbon dioxide emissions (P<0.05), even though the concentration of phytochemical compounds among cultivars was not variable (P>0.05). Implications. Understanding the impact of changing forage chemical composition on reducing greenhouse gas (GHG) emissions in dairy systems is an important issue for mitigating climate change. Conclusions. The inclusion of sorghum silage in this study slightly reduced enteric methane and carbon dioxide emissions. Under these conditions, it is suggested that more information be provided on greenhouse gas emission factors and mitigation strategies in small-scale production systems.